STRENGTHENING HOUSEHOLD FINANCIAL RESILIENCE THROUGH FINANCIAL LITERACY IN PRE-PROSPEROUS WOMEN'S GROUPS IN MALATUNRUNG PALOPO CITY - Goso, Goso (Universitas Bina Taruna Gorontalo, 2022)
Women's financial skills in a household are critical, considering that some of the roles and responsibilities of household financial management usually rest with a woman. The implementation of this guidance to the community aims to strengthen household financial resilience through increasing financial literacy in the pre-prosperous women's group. This service implementation model uses two approaches to overcome partner problems. The first is by using the Heuristic model as a model for financial literacy education and the Enthrepreneurship Capacity Building (ECB) model for empowering partner household entrepreneurship. As a result of the implementation of this community partnership program, there was a fairly good increase in knowledge and understanding of individual finances and household financial management of pre-prosperous women's groups in Malatunrung village compared to what was previously very lacking. The empowerment and resilience of households economically also increase with the skills possessed in utilizing local resources and processing them into products that have high economic value. There was a 100% increase in the new skills of partners who were pre-prosperous women's groups. This community partnership program provides an opportunity to improve individual skills for women that are not acquired in formal education programs, thereby increasing household financial empowerment and resilience that contribute directly to household welfare.